Measurement of the total and differential cross-sections of tt[bar]W production in pp collisions at √s= 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
Measurements of inclusive and differential production cross-sections of a top-quark-top-antiquark pair in association with a W boson (tt[bar]W) are presented. They are performed by targeting final states with two same-sign or three isolated leptons (electrons or muons) and are based on √s= 13 TeV proton-proton collision data with an integrated luminosity of 140 fb−1, recorded from 2015 to 2018 with the ATLAS detector at the Large Hadron Collider. The inclusive tt[bar]W production cross-section is measured to be 880 ± 80 fb, compared to a reference theoretical prediction of 745 ± 50 (scale) ± 13 (2-loop approx.) ± 19 (PDF, αs) fb. Differential cross-section measurements characterise this process in detail for the first time. Several particle-level observables are compared with a variety of theoretical predictions, which generally agree well with the normalised differential cross-section results. Additionally, the relative charge asymmetry of tt[bar]W+ and tt[bar]W- is measured inclusively to be ACrel = 0.33 ± 0.05, in very good agreement with the theoretical prediction of 0.322 ± 0.003 (scale) ± 0.007 (PDF), as well as differentially.
Veröffentlicht: 10. Mai 2024
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, M. Dunford, S.J. Dittmeier, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Im Titel steht der zweite Buchstabe "t" mit einem Oberstrich
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 08.07.2025